INTERPROFESSIONALITY IN HEALTH: THE INTEGRATION BETWEEN PSYCHOLOGY AND NURSING IN THE CARE OF PATIENTS WITH SPINAL CORD INJURY - Evangelista, Ana Karoline Silva; Muniz, Marcela Vilarim; Brasileiro, Maria Luiza do Vale (Seven Editora, 2025)
Interprofessionality in hospital care is an essential element for the qualification of health care, especially in contexts of high complexity, such as the Intensive Care Unit (ICU).  This study aimed to evaluate the interaction between psychologists and nurses in the care of patients with spinal cord trauma in an intensive care unit (ICU), analyzing how the interprofessional collaboration between the two categories contributes to the promotion of comprehensive and quality care. This is a qualitative, descriptive research carried out in a reference hospital in the Federal District. Data collection was conducted through semi-structured questionnaires applied to health professionals and the analysis was based on Bardin's content analysis method. The findings show that interprofessionality is materialized in the exchange of knowledge and collaboration to cope with the physical and emotional adversities of patients. However, challenges such as communication difficulties and job delimitation were identified as obstacles to joint work. It is concluded that strategies aimed at the qualification of communication and the construction of collaborative routines can strengthen the care provided, contributing to a more efficient and humanized care model.DOI: https://doi.org/10.56238/sevened2025.018-013